Analysis of English Loan Words from Asian and European Languages - Rahmat; Resyadi, Herman; Sultan, Arni Arsyad (English Language, Linguistics, and Culture International Journal, 2025)
This research aims to analyse the English loan words from Asian languages (Arabic, Chinese, and Japanese) and European language (French, Italian, and Spanish). This research is a library research, which means that the data were collected from books, thesis, journals, and research articles. This research used qualitative research as the approach and content analysis as the technique. The researcher used documentation as the technique of data collection as the sources of the data is corpus of books, journals, and a research. The result of the data analysis shows that the loan words from Arabic origin had undergone drastic change, the loan words from Chinese origin had not undergone much change, and the loan words from Japanese origin had no any change at all. The loan words from French origin had not undergone much change, the loan words from Italian origin had only one word that undergo a minor change, and the loan words from Spanish origin had undergone minor changes.